Pemanfaatan Buah Berenuk (Crescentia cujete L.) sebagai Kerajinan dan Alat Rumah Tangga di Serang, Banten - Julianti, Maritza; Febriyanti, Kantina; Utami, Regiana; Amelia, Evi; Fitriana, Desi Eka Nur (Jurnal Ilmiah Biologi UMA (JIBIOMA), 2024)
The fruit of the berry (Crescentia cujete) had been widely known by the community. However, the use of this fruit had not been widely explored, especially related to the morphology and anatomy of the fruit, which supported its potential as a sustainable basic material. This study aimed to study the morphology and anatomy of berenuk fruit and explore its use as a basic material for crafts and household tools. The method used was qualitative descriptive, and the sampling technique was purposive sampling. Data was collected through field surveys, interviews with local artisans, and direct observation of the processing and utilization process of berenuk fruits. The data was reinforced through literature studies. The results of the study showed that Berenuk Fruit had great potential in diversifying the local economy, creating business opportunities, and supporting environmental conservation. The morphology and anatomy of the berenuk fruit, such as its hard skin and wide inner cavity, strongly supported the use of this fruit as a raw material for crafts and household tools. Furthermore, it was very necessary to increase people's knowledge and skills regarding processing techniques to maximize the use of berenuk fruit, as well as a good marketing strategy so that this fruit-based product could compete in a wider market.